Targeting Oxidative Stress and Endothelial Dysfunction Using Tanshinone IIA for the Treatment of Tissue Inflammation and Fibrosis. (7th April 2022) - Lu, Tsuo-Cheng; Wu, Yi-Hsiu; Chen, Wei-Yu; Hung, Yu-Chiang
Abstract : Salvia miltiorrhiza Burge (Danshen), a member of the Lamiaceae family, has been used in traditional Chinese medicine for many centuries as a valuable medicinal herb with antioxidative, anti-inflammatory, and antifibrotic potential. Several evidence-based reports have suggested that Salvia miltiorrhiza and its components prevent vascular diseases, including myocardial infarction, myocardial ischemia/reperfusion injury, arrhythmia, cardiac hypertrophy, and cardiac fibrosis. Tanshinone IIA (TanIIA), a lipophilic component of Salvia miltiorrhiza, has gained attention because of its possible preventive and curative activity against cardiovascular disorders. TanIIA, which possesses antioxidative, anti-inflammatory, and antifibrotic properties, could be a key component in the therapeutic potential of Salvia miltiorrhiza . Vascular diseases are often initiated by endothelial dysfunction, which is accompanied by vascular inflammation and fibrosis. In this review, we summarize how TanIIA suppresses tissue inflammation and fibrosis through signaling pathways such as PI3K/Akt/mTOR/eNOS, TGF- β 1/Smad2/3, NF- κ B, JNK/SAPK (stress-activated protein kinase)/MAPK, and ERK/Nrf2 pathways. In brief, this review illustrates the therapeutic value of TanIIA in the alleviation of oxidative stress, inflammation, and fibrosis, which are critical components of cardiovascular disorders.